Internalisasi Nilai-nilai Karakter Religius dan Gotong Royong Siswa melalui Ekstrakurikuler Rohis di SMK-SPP Negeri 3 Kerinci - Mukhlis; Gusril Kenedi; Nursyamsi; Pefriadi (At Turots: Jurnal Pendidikan Islam, 2024)
The undeniable reality of moral decay, particularly among adolescents, seems to persist in the era of scientific and technological advancements, especially within the middle school student population. Therefore, the role of schools extends beyond being institutions solely for acquiring knowledge; they should also be capable of providing education that fosters character development. In an effort to internalize character education values, this school has introduced the extracurricular activity called "Rohis". This research aims to describe the process of internalizing religious and communal character education values through the Rohis Extracurricular Program. The study employs a qualitative approach with a descriptive analysis method. Data collection techniques include observation, interviews, and document analysis. The findings of this research indicate that the internalization process involves several stages, including: 1) the transformation of values, where the material is delivered by knowledgeable teachers or religious leaders using verbal methods such as lectures through Rohis programs like Islamic Studies, Community Service, Quran Guidance, and others; 2) the transaction of values, through active programs where mentors or trainers not only provide material but also engage in practical actions (modeling). There is a reciprocal interaction between mentors and students through programs such as religious discussions, nature contemplation, overnight religious activities (Mabit), and others; 3) the trans-internalization of values, by (a) instilling habitual behaviors, attitudes, and actions in accordance with the imparted values, and (b) promoting positive character values by creating a religious and communal atmosphere within the school.